2005
DOI: 10.1152/ajpheart.00322.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate-fortified cardioplegia suppresses oxidative stress and enhances phosphorylation potential of arrested myocardium

Abstract: Cardioplegic arrest for bypass surgery imposes global ischemia on the myocardium, which generates oxyradicals and depletes myocardial high-energy phosphates. The glycolytic metabolite pyruvate, but not its reduced congener lactate, increases phosphorylation potential and detoxifies oxyradicals in ischemic and postischemic myocardium. This study tested the hypothesis that pyruvate mitigates oxidative stress and preserves the energy state in cardioplegically arrested myocardium. In situ swine hearts were arreste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 49 publications
(59 reference statements)
2
32
0
Order By: Relevance
“…Thus, the impact on free radical formation and release should have been minimized. Under aerobic or reperfusion conditions similar to those existing during pyruvate supplementation in our study, pyruvate is know to elevate or maintain cytosolic ATP phosphorylation potential in part through the modulation of the mitochondrial NADH-to-NAD ratio (15,16). Pyruvate can also enhance carbon substrate delivery to the TCA cycle during aerobic conditions, either through the formation of acetyl-CoA or pyruvate carboxylase.…”
Section: Ischemia-reperfusionsupporting
confidence: 53%
“…Thus, the impact on free radical formation and release should have been minimized. Under aerobic or reperfusion conditions similar to those existing during pyruvate supplementation in our study, pyruvate is know to elevate or maintain cytosolic ATP phosphorylation potential in part through the modulation of the mitochondrial NADH-to-NAD ratio (15,16). Pyruvate can also enhance carbon substrate delivery to the TCA cycle during aerobic conditions, either through the formation of acetyl-CoA or pyruvate carboxylase.…”
Section: Ischemia-reperfusionsupporting
confidence: 53%
“…Recent studies in this model (14,15) demonstrated that pyruvate-enriched cardioplegia acutely increased myocardial pyruvate and ATP contents, PCr phosphorylation potential, i.e., indicator of the redox state of the myocardium's antioxidant systems (32), was increased greater than or equal to twofold (P Ͻ 0.05) 4 h after pyruvate treatment vs. sham and control cardioplegia-treated myocardium (Fig. 2D).…”
Section: Resultsmentioning
confidence: 86%
“…A cannula was inserted into the aortic root for cardioplegia infusion. Crystalloid cardioplegia (pH 7.6) contained 104 mM NaCl, 135 mM NaHCO 3, 91 mM KCl, 6 mM CaCl2, 188 mM glucose, 68 U/l insulin, and 676 mg/l lidocaine (14). Pyruvate cardioplegia was prepared by equimolar substitution of 24 mM sodium pyruvate for NaCl.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations